(untitled) (Palimpsesto, 2020)
This article analyzes the play L’Attente by Miguel Retamal, stating that for the correct understanding of it is necessary to interpret it not as a realistic drama but as a contemporary tragedy, whose argument adresses the experience of exile. The tragic postulates of Albin Lesky are proposed as a theoretical framework to study two inherent themes of exile: the tension between loyalty and fidelity posed by Judith Shklar and the tension produced by the "destiempo" and "desespacio" concepts proposed by Vasquez-Bronfman.